Structural and Thermodynamic Properties of TwoCrystalline Forms of 3-Nitro-1,2,4-triazole-5-one - Eskandari Shahkari, Shahla; Hossein Keshavarz, Mohammad; Bahrami Ghareghani, Sirus (Asian Journal of Chemistry, 2010)
Structural and thermodynamic properties of two crystalline forms of 3-nitro-1,2,4-triazole-5-one (NTO), namely α-NTO and β-NTO, have been determined by ab initio molecular orbital calculations at the Hartree-Fock and density functional theories at the B3LYP/6-31G level. NTO is an important high performance and a thermally stable impact insensitive explosive. Heat capacities, enthalpy, free energy and the other thermodynamic properties of α-NTO and β-NTO are also calculated. The results show that the calculated solid heats of formation and densities, as important input data for calculation of the performance of explosive by thermochemical codes or empirical methods, are comparable with the experimental reported values.